Advancements in Early Alzheimer’s Treatment: Narrative Review about Lecanemab (Leqembi ®) - Muciek, Adrianna; Mocarska, Martyna; Orłowska, Anna; Strakowska, Katarzyna; Opalska, Laura; Maryńczak, Anna; Mencel, Jan; Nitschke, Nicole (Quality in Sport, 2024)
Alzheimer’s disease represents one of the most significant challenges in the field of neurology, affecting millions of individuals worldwide. In pursuing efficacious treatments, lecanemab has emerged as a promising therapeutic option. This pioneering monoclonal antibody targets and reduces amyloid-beta plaques in the brain, a defining feature of Alzheimer’s disease. By addressing one of the fundamental causes of the disease, lecanemab represents a novel approach to slowing its progression. On 14th November 2024, the Committee for Medicinal Products for Human Use (CHMP) adopted a positive opinion, recommending granting marketing authorisation for Leqembi® (whose active substance is lecanemab). This recommendation is specifically directed towards patients with early-onset Alzheimer’s disease who are non-carriers or heterozygotes for the apolipoprotein E ε4 (ApoE ε4) allele, thereby underscoring the drug’s efficacy tailored to specific genetic profiles (Committee for Medicinal Products for Human Use, 2024). The CHMP’s approval is a testament to the extensive research and clinical trials that have demonstrated the efficacy and safety of Leqembi® (Lecanemab). This narrative review aims to provide a comprehensive examination of these aspects and offer a detailed understanding of the potential impact of this treatment on the management of early Alzheimer’s disease.